Analysis of real power allocation for deregulated power system - Samsudin, Mohd Sauqi (2008)
The aim of deregulation in the electric power industry is to optimize the system welfare, by introducing competitive environment, mainly among the suppliers. Developing fair and equitable real and reactive power allocation method has been an active topic of research, particularly in the new paradigm, with many transactions taking place at any time. The current tracing method is chosen because this method is simple and more flexible. Based on solve load flow and network parameter, the method converts power injections and line flow into real and imaginary current networks. This current is represented independently as real and imaginary current networks. Since current network are acyclic lossless networks proportional sharing principle and this method is used to trace the relationship between current sources and current sinks. From this relationship of current components of individual generators, it is possible to find real power contribution of each generator. This method also applied for real power allocation with a few modification. The advantages of the proposed methodologies are demonstrated by commonly used test system and TNB systems. The proposed methodologies provide better reliability and minimize the limitation of conventional real power allocation method.